Row houses : a housing typology - Pfeifer, Günter, 1943- (Birkhäuser, 2008)
To continue developing existing building types in an intelligent way is a crucial task in the field of residential building. A deeper understanding of the underlying types is indispensable for the success of the individual design, as well as for ensuring that tried and tested structures can be utilized, repeated, and varied in a wide variety of situations. For this typology of residential buildings, the authors have developed systematic new presentations of the most innovative types. Each individual volume lays out the possibilities for using and transforming a particular form of residential s.